2023 International Conference on Rehabilitation Robotics (ICORR) 2023
DOI: 10.1109/icorr58425.2023.10304768
|View full text |Cite
|
Sign up to set email alerts
|

VIBES: Vibro-Inertial Bionic Enhancement System in a Prosthetic Socket

Alessia Silvia Ivani,
Federica Barontini,
Manuel G. Catalano
et al.

Abstract: The use of vibrotactile feedback is of growing interest in the field of prosthetics, but few devices fully integrate this technology in the prosthesis to transmit high-frequency contact information (such as surface roughness and first contact) arising from the interaction of the prosthetic device with external items. This study describes a wearable vibrotactile system for high-frequency tactile information embedded in the prosthetic socket. The device consists of two compact planar vibrotactile actuators in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…In the past, a simple transducer attached to a small speaker [4] was proposed, and in recent years, Ueda et al have transmitted the warmth or coldness of an object by transmitting the temperature detected by a temperature sensor at the fingertip to a device on the upper arm [5], Osborn et al developed electronic skin, which can transmit pain to the user by detecting differences in the shape and texture of objects at the fingertips and sending signals to peripheral nerves [6], and various other skin sensations can now be transmitted. Alessia et al measured the acceleration of the fingertip and controlled the oscillator of a socket to enable discrimination of roughness [7], Christian et al detected pressure from a silicon bulb and confirmed that the magnitude of pressure could be discriminated by inflating the silicon pad at the cut using a monofilament [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, a simple transducer attached to a small speaker [4] was proposed, and in recent years, Ueda et al have transmitted the warmth or coldness of an object by transmitting the temperature detected by a temperature sensor at the fingertip to a device on the upper arm [5], Osborn et al developed electronic skin, which can transmit pain to the user by detecting differences in the shape and texture of objects at the fingertips and sending signals to peripheral nerves [6], and various other skin sensations can now be transmitted. Alessia et al measured the acceleration of the fingertip and controlled the oscillator of a socket to enable discrimination of roughness [7], Christian et al detected pressure from a silicon bulb and confirmed that the magnitude of pressure could be discriminated by inflating the silicon pad at the cut using a monofilament [8].…”
Section: Introductionmentioning
confidence: 99%